Source Estimation in the Human Brain from EEG Based on the SSB Head Model - Musha, T.; Ivanov, V.; Konyshev, V. (Methods of Information in Medicine, 1994)
Neuronal activity in the brain cortex is replaced by a small current dipole, and hence the localized electric activities of the cortex are well approximated by equivalent current dipoles. Position and moments of these equivalent dipoles are estimated from the scalp potentials. In this analysis, the head as a conductor is divided into three volumes with uniform electric conductivity: Scalp, Skull and Brain tissue; we call this head model the SSB Head Model. The boundary element method is used in solving this problem and reliability of the final result mainly depends on the arrangement of nodal points on the surfaces of these three regions for numerical calculation, the electric conductivity ratios of the three regions in the model, and the number of electrodes. By means of computer simulation we investigated dependence of errors in the estimated dipole position on these factors. It is found that arrangement of nodal points must be decided adaptively depending on the source position.
Keywords: Dipole Tracing; Head Model; Nodal Points; Conductivity Ratios; Equivalent Dipole